FAKTOR-FAKTOR KESULITAN PENGISIAN SPT MASA DAN PENGARUHNYA TERHADAP KEPATUHAN WAJIB PAJAK DI KECAMATAN PAMEKASAN - Aina, Muslimatul (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
The purpose of this study is to determine the influence of factors difficulty charging tax return on taxpayer compliance in the District Pamekasan. Determination of the number of samples of the taxpayer population in the District Pamekasan with a level of error of 10% as many as 94 taxpayers. The analysis method used is multiple linear regression analysis. Result of hypothesis test by using t test, it is known that variable of instruction of filling SPT Masa (X2) and applicable tax regulation (X4) have significant effect to taxpayer compliance (Y). Where the t count value of instruction variable of SPT Masa (2,897) and applicable tax regulation (1,800) is bigger than ttable value with α 0,05 (1,6612). That the guidance factor of filling SPT Masa has the most dominant effect on taxpayer compliance in Kecamatan Pamekasan. There is another factor of 66,2% which can influence taxpayer compliance, that is tax inspection factor.